2012
DOI: 10.1007/s00289-012-0722-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polypropylene/montmorillonite nanocomposites as food packaging material

Abstract: The aim of this study was to use nanocomposites of polypropylene (PP) and montmorillonite (MMT), prepared by melt intercalation in a twin-screw extruder, as a food packaging material. The nanocomposites were evaluated by thermal, mechanical, and morphological analyses. Measurements of oxygen and water vapor permeability were also conducted to the nanocomposites. Besides, orange juice was used as modeling food and its physical-chemical and microbiological properties were determined. Despite of no significant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The nanoclay also affected the crystallinity of the polymer (Sanchez-Garcia et al 2010 Strawhecker, Manias 2000, Gaume et al 2012, Sapalidis et al 2012. Poly(propylene) (PP) filled with nanoclay displayed an improved barrier performance and the morphology was also affected (Zehetmeyer et al 2012). The same behaviour has been reported for PVOH mixed with nanoclay (Strawhecker, Manias 2000, Yu et al 2003, Johansson, Clegg 2015 and EVOH (Cabedo et al 2004).…”
supporting
confidence: 61%
“…The nanoclay also affected the crystallinity of the polymer (Sanchez-Garcia et al 2010 Strawhecker, Manias 2000, Gaume et al 2012, Sapalidis et al 2012. Poly(propylene) (PP) filled with nanoclay displayed an improved barrier performance and the morphology was also affected (Zehetmeyer et al 2012). The same behaviour has been reported for PVOH mixed with nanoclay (Strawhecker, Manias 2000, Yu et al 2003, Johansson, Clegg 2015 and EVOH (Cabedo et al 2004).…”
supporting
confidence: 61%
“…Although, they have good mechanical and barrier properties towards moisture, it has poor grease resistance and gas barrier properties [49]. Several studies reported that the incorporation of a small amount of OMMT in polyolefin efficiently improved the barrier properties and concurrently enhanced the mechanical and thermal properties due to the impermeable lamellar of nanoclay [50][51][52][53][54][55][56][57]. The finding from Xie et al [58] revealed that although the moisture barrier of the LDPE-OMMT nanocomposite was enhanced by the tortuous path of nanoclay, it also can be reduced when the content of OMMT exceeds a critical value due to the greater capacity of moisture absorption from the remaining hydrophilic part of OMMT.…”
Section: Ethylene-vinyl Alcohol (Evoh)mentioning
confidence: 99%
“…Based on these results, the thermal stability of PCN1, PCN3, and PCN5 was more improved than the PCN0 case by increasing the initial decomposition temperature. However, the onset temperatures (T onset ) decreased as the nanoclay content increased, probably due to the decomposition of ammonium salt in the nanoclay and the nanoclay agglomeration as its content increased [ 36 ].…”
Section: Resultsmentioning
confidence: 99%